Investigation on peculiar SNR variation at TianMa radio telescope - He, Qingbao (Sci Rep, 2019)
Chinese lunar spacecraft Chang’E-3 (CE3) and Chang’E5-T1 (CE5T1) were launched in 2013 and 2014, respectively and very long baseline interferometry (VLBI) observations were performed. Signal to noise ratio (SNR) of the Tianma (TM) station experienced peculiar variation, whereas SNRs of other stations were rather stable. Further, it happened only when observing spacecraft, and showed no such variation when performing astronomical observations. Moreover, it was distinctive on X band signals, whereas it was not noticed on S band signals. Analysis showed that the SNR variation was closely related with changing rate of elevation angle. Further investigations discovered that there were two sets of antenna control software at TM station, and the SNR variation originated from a bug in elevation control software used for observing spacecraft, not for astronomical observations. The bug caused big pointing error (around ± 30 as) on elevation angle of TM, which resulted in the peculiar SNR variation. It was not noticed on S band signals due to its relatively wide and flat main beam comparing with ± 30 as pointing error. However, the bug was fixed in software update in July, 2016, and the SNR of TM showed no such variation in 2017 and 2018.